A Concise Survey of German Literature - Garland, H.B. (Coral Gables University of Miami Press, 1971)
The book sets out to cover in a small compass the rise and development of German literature from the beginnings to the present day. The aim has been to write a book of a size and tone which would allow it to be read if necessary at a sitting and quite easily in two or three goes.
Keywords: German